Competing Ideologies and Reforms in Traditional Medicine from 1948-1960: Abeyrathne R.M.* (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
Those who involved in reforming Traditional Medicine in Sri Lanka believed that informally trained (Deshiya Chikithsa) practitioners and Ayurveda practitioners were able to create a common platform to reform if after independence. Nevertheless, traditional medicine became a highly contested phenomenon in the aftermath of independence from 1948-1960. The objective of this study was to study how the reforms proposed by the so-called progressive front led by Dr. Lenora and others became highly controversial issues between 1948 and 1960. This research project was carried out as a qualitative study at various institutes in the United Kingdom and Sri Lanka. The researcher of this study used a digital camera to film all relevant material at various institutes and organized them into logical themes and analysed them according to theme-list and content analysis methods. This study findings reveal that the existing ideologies between the two opposing groups discouraged them to reach a common platform bring about syntheses to safeguard the Ayurveda system of Medicine and Deshiya Chikithsa for the betterment of the country. Therefore, the focus of reforms was, therefore, what can be referred to as the ‘biomedicalization’ of TM; an approach that continued to stoke tensions among politicians, administrators, and TM practitioners. Therefore, these research findings speak the need of conducting research to identify ways to create harmonious grounds to bridge Ayurveda and Deshiya Chikithsa with modern scientific methods without losing the authenticity of the two for the benefit of the people of Sri Lanka. Keywords: Ayurveda, Deshiya Chikitsa, reforms, practitioners, progressive